Un auteur, une chronique, un destin : Diego de Rosales et le Chili - Thierry Nouaille (Caravelle)
In 1674, Father Diego de Rosales completed his manuscript entitled Historia General del Reino de Chile, Flandes Indiano. For almost half a century, he had been the actor and witness of the Arauco war and evangelizing of the natives. Though it was cut in its final chapters, the chronicle came up us despite trials and tribulations.